Factors contributing to the successful implementation of management innovations - Zekić, Zdravko (Mednarodna revija za javno upravo, 2017)
The concept of management innovation as distinctive type of non- technological innovations is still in the early days of conceptual formation and confirmation. This paper aims to investigate the concept of mana% gement innovations in public sector organizations with an emphasis on identifying the impact of organizational factors on the successful implementation of management innovations. The aim of implementation of new management concepts and methods is to increase efficiency and effectiveness of public services. A research was conducted on a sample of local self%government units in Croatia using empirical methods. The obtained results confirm the set conceptual determinants of the management innovation term, as manifested through the influence of selected organizational factors. Accordingly, absorptive capacity and top management support, with the combined effects of implementation climate and innovation-values fit, have been identified as key factors to achieving successful implementation of management innovations. On the other hand, availability of significant financial resources was not found to be a significant factor for the effective implementation of this type of innovation. Research results suggest theoretical and practical implications for strengthening the effectiveness of local self-government
Keywords: effectiveness; innovations; inovacije; local government; lokalna samouprava; mamangement; management; učinkovitost